2022
DOI: 10.1186/s12575-022-00176-w
|View full text |Cite
|
Sign up to set email alerts
|

Circ_0003570 Suppresses the progression of hepatocellular carcinoma through miR-182-5p/STARD13 regulatory axis

Abstract: Background Emerging evidence have revealed that circRNAs exert important biological effects in the development and progression of various diseases, including cancer. Our study aimed to elaborated the biological effects of hsa-circ_0003570 in hepatocellular carcinoma (HCC) development at the molecular level. Results The results of functional experiments showed that knockdown of circ_0003570 induced HCC cell growth, migration and invasion, whereas ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…In a previous study, the high expression of miR-182-5p activated the Wnt/β-catenin signaling pathway by interfacing with β-catenin degradation, leading to unfavorable prognoses, including early recurrence in HCC patients that underwent surgery [25]. Recently, Zhang et al demonstrated that the overexpression of circ_0003570 suppressed HCC progression by regulating the miR-182-5p/STARD 13 axis [26]. Similar to the tumor suppressor role of hsa_circ_0004018 by inhibiting the Wnt/β-catenin signaling pathway, hsa_circ_0003570 may function as an HCC tumor suppressor by sponging miR-182-5p, leading to the inactivation of Wnt/β-catenin signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, the high expression of miR-182-5p activated the Wnt/β-catenin signaling pathway by interfacing with β-catenin degradation, leading to unfavorable prognoses, including early recurrence in HCC patients that underwent surgery [25]. Recently, Zhang et al demonstrated that the overexpression of circ_0003570 suppressed HCC progression by regulating the miR-182-5p/STARD 13 axis [26]. Similar to the tumor suppressor role of hsa_circ_0004018 by inhibiting the Wnt/β-catenin signaling pathway, hsa_circ_0003570 may function as an HCC tumor suppressor by sponging miR-182-5p, leading to the inactivation of Wnt/β-catenin signaling pathway.…”
Section: Discussionmentioning
confidence: 99%